Japan’s new competitive advantage: the arguments and proposals for structural reorientation - Młodawska, Jolanta (Comparative Economic Research. Central and Eastern Europe, 2010)
As forecasted by the Japanese government, the country’s economy will grow, although slowly. This expectation is determined by the risk that the labour market situation and the worldwide business cycle will keep deteriorating. It is believed that the economy will not be spurred by exports growing as a result of worldwide recovery, but rather by a series of stabilization packages and gradually expanding domestic demand61. The expectations should be treated with a great deal of cautiousness, because of the highly unpredictable rate of unemployment, the concerns about deflation and the probability of the global recession turning out more serious than expected. According to the AFP (Gazeta Wyborcza of 08 Dec. 2009), in the third quarter of 2009 the Japanese economy finally showed some signs of recovery and reached positive values; unemployment also dropped from 5.3% to 5.1% between September and October. The widespread opinion is that the recovery is very fragile, as proved by the steadily falling prices, deflation, and the rising yen exchange rate (the highest in the last 14 years – 84 yen to 1 US dollar), threatening the Japanese exports.